Development of E-Modules Assisted by Smart Apps Creator on Reproductive System Material to Improve Cognitive Abilities and Self-Awareness Attitudes towards Reproductive Health of Class XI SMA/MA Learners - Nurul Qomariyah; Kartika Ratna Pertiwi (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted using the ADDIE development model. The development design consists of 5 stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The subjects for limited trial were 30 students of class XII IPA MAN 1 Yogyakarta, while for a wide-scale trial, they were of 58 students of class XI IPA MAN 1 Yogyakarta. Data collection techniques used in this study were observation, interviews, questionnaires, tests, and documentation. The data from this study were analyzed using by Manova test. The results of this study indicate that, 1) e-modules assisted by smart apps creator on reproductive system is declared feasible for use in the process of learning activities, 2) e-modules assisted by smart apps creator on reproductive system material are declared practical for use in the learning activity process, 3) e-modules assisted by smart apps creator effectively improve cognitive abilities and self awerness attitude towards reproductive health with an N-Gain value of 57.7 and 56.4, respectively (fair category). The Manova test indicates a Sig. 0.000 meaning there is a significant difference in cognitive abilities and self-awareness attitudes towards reproductive health of students who use and do not use e-modules assisted by smart apps creator.